Role of symbiotic auxotrophy in the Rhizobium-legume symbioses. - Jurgen Prell; Alexandre Bourdès; Shalini Kumar; Emma Lodwig; Arthur Hosie; Seonag Kinghorn; James White; Philip Poole (PLoS ONE)
Background Rhizobium leguminosarum bv. viciae mutants unable to transport branched-chain amino acids via the two main amino acid ABC transport complexes AapJQMP and BraDEFGC produce a nitrogen starvation phenotype when inoculated on pea (Pisum sativum) plants [1], [2]. Bacteroids in indeterminate pea nodules have reduced abundance and a lower chromosome number. They reduce transcription of pathways for branched-chain amino acid biosynthesis and become dependent on their provision by the host. This has been called "symbiotic auxotrophy". Methodology/principal findings A region important in solute specificity was identified in AapQ and changing P144D in this region reduced branched-chain amino acid transport to a very low rate. Strains carrying P144D were still fully effective for N(2) fixation on peas demonstrating that a low rate of branched amino acid transport in R. leguminosarum bv. viciae supports wild-type rates of nitrogen fixation. The importance of branched-chain amino acid transport was then examined in other legume-Rhizobium symbioses. An aap bra mutant of R. leguminosarum bv. phaseoli also showed nitrogen starvation symptoms when inoculated on French bean (Phaseolus vulgaris), a plant producing determinate nodules. The phenotype is different from that observed on pea and is accompanied by reduced nodule numbers and nitrogen fixation per nodule. However, an aap bra double mutant of Sinorhizobium meliloti 2011 showed no phenotype on alfalfa (Medicago sativa). Conclusions/significance Symbiotic auxotrophy occurs in both determinate pea and indeterminate bean nodules demonstrating its importance for bacteroid formation and nodule function in legumes with different developmental programmes. However, only small quantities of branched chain amino acids are needed and symbiotic auxotrophy did not occur in the Sinorhizobium meliloti-alfalfa symbiosis under the conditions measured. The contrasting symbiotic phenotypes of aap bra mutants inoculated on different legumes probably reflects altered timing of amino acid availability, development of symbiotic auxotrophy and nodule developmental programmes.